Investigation of abundant treated sea sand (ATSS) with different percentages in cement brick ratio 1:6 - Khairul Danial, Abd. Latif (2010)
Nowadays the high demand of river sand is an indication of development especially for the construction industry. Therefore, it is needed an alternative way in fulfill this condition. However, from the study, it stated that the quantity of the river sand became slowly decrease. Thus, the alternative that is viable to replace the river sand is by using the sea sand. In applying this alternative, the chloride content and the sea sand shape particles are the major problems that should be taken note. High level of chloride content is possibility affecting the strength of the construction structure. Therefore the sea sand that will used should be washed first to reduce the chloride content for a particular period of time. In the basic structure material, they are already having their own limitation of chloride level. This is to ensure that the construction structure such as reinforcement bars would not corrode in the concrete. In the cement brick manufacture, the high rate of chloride content will affected the strength of the brick because the Portland cement also have its own chloride content. Brick is one of the basic normal structures in the building. In this study, there are several experiments need to be performed to determine the chloride content and the grading size of the abundant treated sea sand ( ATSS ).The compressive strength and the water absorption testing also need to be performed in order to study the comparison strength by using river sand and the sea sand. The ratio cement to sea in this study is 1:6. The brick size that been used was 2 15mm x 102.5mm x 65mm which is work size stated in British Standard (BS). The result showed that the properties and strength of the sea sand brick samples have exceeded the minimum strength required.